Frosted Branch Angiitis (FBA): A case report (Community Based Medical Journal, 2021)
The purpose of the study is to describe a rare case report for raising the awareness of existence of this rare ocular disease and also review the characteristics of this disease.  A 35-year-old man presented with acute vision loss in both eye after high grade fever. On fundoscopic examination flower petal pattern blood vessel sheathing in temporal quadrant of both eyes was seen. A provisional diagnosis of frosted branch angiitis was considered. The patient responds promptly with Intravenous and oral corticosteroid. A total of 58 cases have been reported in worldwide literature. The disease is likely to represent a common immune pathway in response to multiple infective agents.CBMJ 2020 July: Vol. 09 No. 02 P: 42-44